Pengembangan Aplikasi Pemesanan Jasa Instruktur Olahraga Kota Malang Berbasis Web - Tiara Rossa Diassananda; Bayu Priyambadha; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sport is one of the activities to improve the quality of life and physical and spiritual health. In the present era in doing sport activities can are given various facilities including: imitating tutorials on youtube or hiring a sports instructor. From the results of interviews with 14 sports instructors in the City of Malang, the obstacles to marketing their services were the limited information dissemination and rapid competition and development in the world of sports instructors.And the survey result of respondents in the city of Malang which is divided into 3 circles are public, students and coeds of men and women,83.8% of them like zumba, aerobic, yoga, gym, swimming, muaythai and 60.6% of them need a sports instructor in conducting the sport activities but 63.4% of them encountered problems in the search for sports instructors are difficult to find a profile instructor, lack of reference, difficult to find an instructor who can adapt to our schedule and lack of instructor pricing information per training session. The developed solution is to develop a web-based sports instructor service application with waterfall software development cycle. Applications built using a web-based basis make it easy to access many platforms on the computer. In the process of engineering needs obtained 54 your functionality with 4 actors inside and 1 non functional needs. Test results blackbox testing obtained 100% valid against the functionality of the application. Test results of whitebox testing were obtained low probability levels against the error. And test result non functional testing compability indicates the application does not encounter errors against the browser tested. Based on these results it can be concluded that this application deserves to be the solution of the problems that occur.